Socioterritorials forms of appropiation of living and right to the differencial space - Núñez, Ana (Universidad del Rosario, 2011)
The aim of this work is to recover Henri Lefèbvre's methodological contributions for (re)thinking the right to the city, based on the need to know the appropriation of space´s dialectical triad. Empirically, it refers to the urban genesis of Mar del Plata (Argentina), an intermediate Latin American city, and its heterogeneous socio-territorial forms of appropriating inhabitance, or different forms of appropriating goods of use, that lead to think about opening to the transformation of the capitalist social order, and of its urban order, naturalized after the fetischism of private property.